The effect and safety of placental blood drainage as a part of active management of third stage of labour in spontaneous vaginal delivery - Gupta, Nidhi; Agarwal, Mohita; Singh, Saroj; Gangwar, Parul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: In placental cord drainage facilitates placental delivery in both vaginal and caesarean section deliveries. The present study was done to evaluate the effect and safety of placental blood drainage as a part of active management of third stage of labour to reduce the duration and blood loss during third stage of labour. Methods: The study was conducted in department of Obstetrics and, SN Medical College, Agra, Uttar Pradesh, India on 400 term pregnant women, with single live intrauterine fetus in cephalic presentation, without any complication. They were randomly divided into to study and control group. Study group: It comprised of 200 Gynaecology cases, underwent active management of third stage of labour with placental blood drainage. Control group: It comprised of 200 cases, underwent active management of third stage of labour (AMTSL) alone. Duration and blood loss during third stage were noted. Results: The mean duration of third stage of labour was 3.61±0.972mins in study group and 8.15±1.711mins in control group. The mean blood loss during third stage of labour was 168.14±76.703ml and 287.40±85.808ml in study and control group respectively. Conclusions: Duration of third stage, blood loss during third stage, and hemoglobin deference between pre and post-delivery were reduced significantly in study group than control group.